A case-control study on rosacea and vitamin D levels - Gürel, Gülhan; Karadöl, Müjgan; Çölgeçen, Emine (Journal of Surgery and Medicine, 2018)
Aim: Rosacea is a chronic inflammatory dermatosis characterized by several features such as temporary erythema (flushing), permanent erythema, papules, pustules and telangiectasia in the face. In this study, our aim is to investigate the role of serum vitamin D levels in the pathogenesis of rosacea. Methods: 50 patients with rosacea and 50 age and gender matched healthy controls were included in this study. In patients with rosacea and control group, serum parathyroid hormone (PTH), vitamin D levels and serum calcium levels were measured and the results were compared statistically. Results: Serum vitamin D levels in patients with rosacea were significantly higher than the control group (respectively 10,55 ng/ml and 8,50 ng/ml). The median of serum calcium level was found to be 8,20 mg/dl in the group of patients with rosacea and 8,55 mg/dl in the control group. Serum calcium levels of the control group were significantly higher than the group of patients with rosacea. There was no statistically significant difference in terms of serum parathormone levels between the group of patients with rosacea and control group. The increase in serum vitamin D levels may lead development of rosacea. Conclusion: As a result, the increase in serum vitamin D levels is associated with rosacea.